Calcium Carbonate Crystallization on a Microalgal Matrix: The Effects of Heavy Metal Presence - Panagiota D. Natsi; Petros G. Koutsoukos (Crystals, 2022)
Microalgae and other microorganisms often play a significant role in the transportation of heavy metal ions in the environment, while at the same time they are closely related to the formation of minerals in aquatic systems, especially with the formation of calcium carbonate (CaCO3). The biomineralization of calcite was investigated in aqueous solutions, supersaturated with respect to calcium carbonate (7.94 < SRcalcite < 31.36) in the presence of heavy metals (Zn, Cd, Ni, Cu) and of colonies of Acutodesmus obliquus (A. obliquus). The presence of metals tested in the supersaturated solutions, at concentration levels below the threshold of precipitation of the respective hydroxides, reduced the rate of calcium carbonate precipitation by 40 to 90% depending on the solution supersaturation. The presence of A. obliquus culture increased the rates of calcium carbonate precipitation by 80%. The presence of the test metals inhibited the growth of A. obliquus, especially the presence of Cd. The uptake of the test metals on calcite fitted Langmuir adsorption isotherm. Cadmium uptake onto calcite reached 85% of the total amount in the solutions. Charged ion pairs of test metals play an important role in their activity with respect to calcium carbonate precipitation and algal growth.